ENHANCING GLOBAL WARMING EDUCATION THROUGH A DISCOVERY LEARNING-BASED HEYZINE FLIPBOOK E-MODULE - Hasibuan, Nurkholijah Rohma; Siagian, Sahat; Tanjung, Samsidar (UNDIKMA, 2025)
This research aims to develop a Discovery Learning-based physics E-module using the Heyzine Flipbook platform to improve student learning outcomes on the topic of global warming in Grade X at SMAN 12 Medan. The development model used is the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through expert validation, practicality questionnaires for teachers and students, and pretest-posttest evaluations to measure effectiveness. The feasibility test results from content, design, and media experts indicated that the E-module is in the